Double Approach Technique for Cervicovaginal Agenesis: A Case Report - Priyatini, Tyas; D. Irsat Syafardi (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Cervicovaginal agenesis is rare female congenital anomalies. The patients usually present with primary amenorrhoea, cyclical abdominal pain, or primary infertility. A conservative surgical approach has been proposed to alleviate obstructive symptoms, construct, and maintain the patency of the genital tract, while still preserving fertility. Case Report: A Ms. 14 year old was referred with primary amenorrhea and cyclical abdominal pain for 5 months. Physical examination and ultrasound revealed cervical dysgenesis with proximal vaginal dygenesis. Cervical canalization using double approach (laparotomy and trasnvaginally) was done to restore the normal anatomical integrity, maintain the functional cervical canal with a theoretical advantage of protection from ascending infection, and preservation of fertility. Discussion: Obstructed menstrual blood, causing symptoms such as primary amenorrhea, could be a sign of female congenital anomalies. Hysterectomy has been the mainstay treatment for many decades, due to the risk of reoperation. Advances in surgical technique of conservative treatment marked the overall success rate up to 60% with few cases are reported to have pregnancy. Conclusions: Double approach technique could be a feasible option for conservative surgery in cervicovaginal agenesis.